Heat transfer performance of green bio-glycol based TiO2-SiO2 nanofluids - Siti Nursharah, Muhamad Zainon (2021)
The dispersion of nanoparticles in conventional heat transfer fluids has been proven to improve the heat transfer performance of the fluids. In order to investigate their ability to enhance thermal performance, various studies have been conducted over the past few decades using single and hybrid nanofluids suspended in various types of base fluids such as water, ethylene glycol, and propylene glycol. However, study on the thermal properties of nanoparticles dispersed in the mixture of water and green Bio-glycol are limited in the literature and only available for single nanofluids. The study showed that Bio-glycol offers greater thermal stability while possessing similar or better physical properties compared to conventional glycol. The purpose of this study is to investigate the stability, thermo-physical properties, heat transfer performance and friction factor of green Bio-glycol based TiO2-SiO2 nanofluids. The hybrid nanofluids was prepared at various volume concentrations ranging between 0.5 and 3.0% by dispersing TiO2 and SiO2 nanoparticles in the mixture of 60:40 of water: Bio-glycol (W/BG). Then, the single nanofluids were mixed at composition ratio of 20:80. The thermal conductivity, dynamic viscosity and density of green Bio-glycol based TiO2-SiO2 nanofluids were measured using specific measuring equipment. While the experimental study on forced convection heat transfer was done under turbulent flow at constant heat flux for the range of Reynolds number between 2,300 and 24,000 and operating temperatures of 30, 50 and 70 °C. Experimental result shows the stability of green Bio-glycol based TiO2-SiO2 nanofluids showed physically to be in good range of stability for suspension nanoparticles with zeta potential of -53.46 mV. The thermal conductivity of the green Bio-glycol based TiO2-SiO2 nanofluids was enhanced up to 12.52% higher than the mixture of W/BG at 3.0% volume concentration and temperature of 70 °C. Meanwhile, there is insignificant dynamic viscosity increment of the green Bio-glycol based TiO2-SiO2 nanofluids with temperature, in which the minimum dynamic viscosity was observed for 0.5% volume concentration and temperature of 80 °C. The density of the nanofluids increases with volume concentration but decreases with temperature rise. The maximum heat transfer enhancements of green Bio-glycol based TiO2-SiO2 nanofluids at different bulk temperatures of 30, 50 and 70 °C were observed to be up to 128.1%, 73.95%, and 67.81%, respectively for 2.5% volume concentration. A slight friction factor escalation of green Bio-glycol based TiO2-SiO2 nanofluids was observed with 12% maximum increment. New correlations were developed to estimate the thermal conductivity, dynamic viscosity, Nusselt number, and friction factor of green Bio-glycol based TiO2-SiO2 nanofluids. The equations showed good accuracy with average deviations of less than 4.3%. As a conclusion, the TiO2-SiO2 hybrid nanoparticles in water/Bio-glycol mixture base fluids was confirmed to be in good stability condition. The properties of the green Bio-glycol based TiO2-SiO2 nanofluids with variation of volume concentration and temperature were improved significantly. The employment of the eco-friendly coolant nanofluids in improving thermal performance is proven and applicable for turbulent forced convection heat transfer applications. Hence from the present study, the utilization of the green Bio-glycol based TiO2-SiO2 nanofluids at 2.0 to 2.5% volume concentration was recommended for various engineering applications.